Synthesis, Characterization And Fouling Evaluation On Superhydrophobic Coating Modified Using Carbon Soot - Mohd Hanapi, Muhamad Syafik (Universiti Sains Malaysia, 2021)
Superhydrophobic coating is an idea that imitate the surrounding nature, whichn has the biggest advantage in corrosion prevention on metals. This is because the surface of contact and liquid can be minimized so it can offer great resistance to humid surrounding. This thesis are to know the superhydrophobic can be achieve surface on the carbon soot from candle flames. The samples later are being dipped into PVDF/Acetone mixture to improve superhydrophobic contact. Carbon Soot(CS) that coating the glass slides which are obtained as hydrophobic state. It is collected from general uses candles to prove the hydrophobic behaviour from the carbon soot collected. Micropipette are being used to drop a few of droplets on the surface to check the contact angle occurred on the surface of carbon soot. The polymer used are 0.8g of Polyvinylidene Fluoride (PVDF) are mixture properly and continuously until it achieved perfect dilute in 80ml of Acetone based. The dip-coating process are in the constant Withdrawal/Drawing (W/D) at 40 mm/s and taking at 4 mins. The drying process are done in whole day time at room temperature. The contact angle on the both surfaces of samples can be obtained through Microscopic lens. As conclusion, carbon soot from candles can achieve hydrophobic and can achieve superhydrophobic with mixture of PVDF/Acetone in certain conditions.